PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING (CTL)TERHADAP HASIL BELAJAR IPS DI SEKOLAH DASAR - Fauzia, Ulfa; mansurdin, mansurdin; faridas, faridas (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The recearch is aimed to know about the influence of using of Contextual Teaching and Learning(CTL) model toward the result of IPS student in grade V at SDN 15 Ampang Gadang Agam The research design of the research is quasy exsperimental design. Sample of the research is class VA and VB. The coubting result of research of data that used is t testfounded t count> ttable(1,7583>1,68830)at α level of 0.05. So that, it can be concluded that there is a significant influence in using Contextual Teaching and Learning(CTL) model toward the result of student’s IPS study in grade V SDN 15 Ampang Gadang Agam Keywords: Contextual Teaching and Learning(CTL), Learning Outcome, IPS